Pengaruh Sistem Bagi Hasil Deposito Terhadap Persepsi Nasabah di Bank BRI Syariah - Sihaloho, Maria; Sitinjak, Santa Fransiska; Sitorus, Rosmawanti; Pasaribu, Debora Enjelina; Putri, Synthia Eppata; Tanjung, Tiodora; Sormin, Restu; Hasugian, Christnova; Siallagan, E Hamonangan (Peneliti.net, 2024)
Banking is a financial institution that provides services and convenience to its customers who want to conduct financial transactions. Bank Syariah Mandiri is one of the Islamic financial institutions that offers mudharabah term deposits (deposits) with profit sharing contracts. This study aims to determine the effect of the deposit profit sharing system on customer perceptions at Bank BRI Syariah. This research uses quantitative methods with 100 respondents. Based on the results of the calculation, the correlation between profit sharing and customer perception has a positive relationship. Then there is a significant influence between profit sharing on customer perception at Bank BRI Syariah.